Leaf-cutting ant faecal fluid and mandibular gland secretion: effects on microfungi spore germination - Rodrigues,André (2008)
The mandibular gland secretion (MGS) and the faecal fluid (FF) of the leaf-cutting ant Atta sexdens rubropilosa Forel affected the spore germination of selected microfungi isolated from nests of this insect. MGS was more effective than the FF, completely inhibiting the spore germination of four out of six microfungi species.